(untitled) (Tanzania Journal for Population studies and Development, 2016)
The mining regime in Tanzania was reformed in the 1990s with the promise that the sector would be a game changer in the efforts to promote economic growth and poverty reduction. Yet, as time went by, it became apparent that the state was shortchanged in the design of mining codes that are tilted in favour of multinational companies when it comes to getting tangible benefits. With evidence from documents and interviews of informed persons, this article traces the footprints of key actors whose interests were decisive in shaping the emerging mining regime. It shows that the lopsided nature of the regime is not a mere coincidence but a calculated initiative to ensure that multinational companies control the mineral resources of the country.